Analysis of Hospital Resource Availability and COVID‐19 Mortality Across the United States - Alexander T. Janke; Hao Mei; Craig Rothenberg; Robert D. Becher; Zhenqiu Lin; Arjun K. Venkatesh (2021)
Although the impact of COVID‐19 has varied greatly across the United States, there has been little assessment of hospital resources and mortality. We examine hospital resources and death counts among hospital referral regions from March 1 to July 26, 2020. This was an analysis of American Hospital Association data with COVID‐19 data from the New York Times . Hospital‐based resource availabilities were characterized per COVID‐19 case. Death count was defined by monthly confirmed COVID‐19 deaths. Geographic areas with fewer intensive care unit beds (incident rate ratio [IRR], 0.194; 95% CI, 0.076‐0.491), nurses (IRR, 0.927; 95% CI, 0.888‐0.967), and general medicine/surgical beds (IRR, 0.800; 95% CI, 0.696‐0.920) per COVID‐19 case were statistically significantly associated with an increased incidence rate of death in April 2020. This underscores the potential impact of innovative hospital capacity protocols and care models to create resource flexibility to limit system overload early in a pandemic.